2015
DOI: 10.1097/md.0000000000001559
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Lactate Threshold in Healthy Young Men as Related to Oxygen Uptake Kinetics

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…The mean BLa increase at the GET was approximately 0.5 mmol/L above the resting level, which is consistent with the results of our and others' previous reports [3,4,5]. Therefore, we can say that this GET level of exercise induces only minimal lactate elevation during Inc-Ex.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean BLa increase at the GET was approximately 0.5 mmol/L above the resting level, which is consistent with the results of our and others' previous reports [3,4,5]. Therefore, we can say that this GET level of exercise induces only minimal lactate elevation during Inc-Ex.…”
Section: Discussionsupporting
confidence: 92%
“…Boehringer Ingelheim, Gaithersburg, MD) was applied to three ngers of the left hand (2nd, 3rd, and 4th ). After 10 min, the cream was removed and the entire left hand, including the distal part of the forearm, was placed in a water bath at 43-45 °C for 10 min [3,14]. BLa levels were determined using Lactate Pro LT-1730 (Arkray, Kyoto, Japan).…”
Section: Blood Lactatementioning
confidence: 99%
See 1 more Smart Citation
“…When more than one such parallel lines were observed, the first one was always taken as S1, the end of which is the VAT. The VAT thus determined best agreed with the lactate threshold in the study we previously reported [7]. Ventilatory equivalent and end-tidal gas concentration plots were also utilized, primarily for the detection of hyperventilation, which breaks the V-slope leftward and may be interpreted as a VAT point.…”
Section: Methodssupporting
confidence: 63%
“…The hypothesis that the S1 is parallel to the diagonal R = 1 was tested as described [ 10 ]. After all of the VAT points and S1 data points (those visually interpreted as being located on or around the hypothetical S1 line parallel to R = 1) had been finalized, the mean of the S1 slopes was tested against the slope of 1.0.…”
Section: Methodsmentioning
confidence: 99%